Conceptual replication and extension of health behavior theories' predictions in the context of COVID-19: evidence across countries and over time - Abakoumkin, Georgios; Tseliou, Eleftheria; McCabe, Kira O; Lemay Jr., Edward P; Stroebe, Wolfgang; Agostini, Maximilian; Belanger, Jocelyn J; Gutzkow, Ben; Kreienkamp, Jannis; Kutlaca, Maja; vanDellen, Michelle R; Abdul Khaiyom, Jamilah Hanum; et al. (Wiley-Blackwell, 2023)
Virus mitigation behavior has been and still is a powerful means to fight the COVID-19 pandemic irrespective of the availability of pharmaceutical means (e.g., vaccines). We drew on health behavior theories to predict health-protective (coping-specific) responses and hope (coping non-specific response) from health-related cognitions (vulnerability, severity, self-assessed knowledge, efficacy). In an extension of this model, we proposed orientation to internal (problem-focused coping) and external (country capability) coping resources as antecedents of health protection and hope; health-related cognitions were assumed as mediators of this link. We tested these predictions in a large multi-national multi-wave study with a cross-sectional panel at T1 (Baseline, March-April 2020; N = 57,631 in 113 countries) and a panel subsample at two later time points, T2 (November 2020; N = 3097) and T3 (April 2021; N = 2628). Multilevel models showed that health-related cognitions predicted health-protective responses and hope. Problem-focused coping was mainly linked to health-protective behaviors (T1-T3), whereas country capability was mainly linked to hope (T1-T3). These relationships were partially mediated by health-related cognitions. We conceptually replicated predictions of health behavior theories within a real health threat, further suggesting how different coping resources are associated with qualitatively distinct outcomes. Both patterns were consistent across countries and time.